Prospect of Corn Flour Utilization to be Chips Through Citizen Training in Antang district, Makassar - Nahriana, Nahriana (International Journal of Education, Vocational and Social Science, 2023)
This research is an experimental research that has objectives to know the process of making the corn flour, to know the making of chips from corn flour, to know the panelists acceptance to corn chips and to know citizens’ opinion to corn chips. This research uses some samples they are, 20 housewives and 15 organoleptic panelists which consist of 5 expert panelists, 5 trained panelist and 5 untrained panelists. Data collecting technique uses score sheet, questionnaire and documentation. Analyzing data technique that is used is quantitative descriptive analyzing technique. The result of this research conclude that the process of making corn flour are ingredient and tool preparation, ingredient weighing, making and shaping the chips, frying and packaging the chips. The best formula based on scoring of the panelists is 50% substitution of corn flour and 50% substitution of glutinous rice flour with 96% color presentation, 85% aroma, 89.33% texture and flavour 95.67%. Based on training that has been done in Antang district, Makassar that the citizen gave positive respond and prospect of corn flour utilization to be chips can give a new alternative in corn processed and can help the economic condition of the citizen.